Experimental investigation of the impact of non-uniform pipe diameters on natural circulation and dimensionless flow in in a rectangular loop - Roswandi, Iwan; Pamitran, Agus Sunjarianto; Juarsa, Mulya; Budiman, Arif Adtyas (Politeknik Negeri Lhokseumawe, 2025)
This experimental study investigates the effect of non-uniform pipe diameters on natural circulation flow within a rectangular loop related to non-dimensional numbers, such as the Reynolds number and the Grashof number. The study aims to understand how variations in pipe diameters influence natural circulation, which is critical for thermal engineering applications, including passive cooling systems for nuclear reactors and thermal management in electronic devices. Previous research by Vijayan et al., Garibaldi et al., and Elton et al. explored the impact of loop geometry on flow stability and heat transfer efficiency. In this study, a loop system with varying pipe diameters operates without a pump at atmospheric pressure. Data on fluid flow and temperature distribution were recorded at different temperature settings. The results show that fluid flow increases with temperature, decreasing fluid density and enhancing buoyancy forces. This increases the Reynolds number, reaching turbulent flow at 70°C throughout the loop. However, the 2-inch diameter hot leg remains in the transition region up to 90°C. The experimental correlation shows higher Grashof numbers than previous models, highlighting the significant impact of pipe diameter variations on buoyancy forces and flow transitions. These findings emphasize the importance of non-uniform pipe geometries in influencing natural circulation flow and its transition from laminar to turbulent flow, providing valuable insights for designing systems with non-uniform pipe configurations.